The condemnation of blackness: race, crime, and the making of modern urban America - Muhammad, Khalil Gibran (Harvard University Press, 2010)
"The Idea of Black Criminality was crucial to the making of modern urban America. Khalil Gibran Muhammad chronicles how, when, and why modern notions of black people as an exceptionally dangerous race of criminals first emerged. Well known are the lynch mobs and racist criminal justice practices in the South that stoked white fears of black crime and shaped the contours of the New South. In this illuminating book, Muhammad shifts our attention to the urban North as a crucial but overlooked site for the production and dissemination of those ideas and practices." "Following the 1890 census - the first to measure the generation of African Americans born after slavery - crime statistics, new migration and immigration trends, and symbolic references to America as the promised land were woven into a cautionary tale about the exceptional threat black people posed to modern urban society. Excessive arrest rates and overrepresentation in northern prisons were seen by many whites - liberals and conservatives, northerners and southerners - as indisputable proof of blacks' inferiority. What else but pathology could explain black failure in the land of opportunity? Social scientists and reformers used crime statistics to mask and excuse anti-black racism, violence, and discrimination across the nation, especially in the urban North." "The Condemnation of Blackness is the most thorough historical account of the enduring link between blackness and criminality in the making of modern urban America. It is a startling examination of why the echoes of America's Jim Crow past continue to resonate in "color-blind" crime rhetoric today."--BOOK JACKET